Influential articles in autism and gut microbiota: bibliometric profile and research trends - Ying, Jiangbo; Zhang, Melvyn Weibin; Wei, Ker-Chiah; Wong, Sunny H.; Subramaniam, Mythily (Frontiers in Microbiology, 2025)
ObjectiveAutism spectrum disorder (ASD) is a common neurodevelopmental disorder. Increasing evidence suggests that it is potentially related to gut microbiota, but no prior bibliometric analysis has been performed to explore the most influential works in the relationships between ASD and gut microbiota. In this study, we conducted an in-depth analysis of the most-cited articles in this field, aiming to provide insights to the existing body of research and guide future directions.MethodsA search strategy was constructed and conducted in the Web of Science database to identify the 100 most-cited papers in ASD and gut microbiota. The Biblioshiny package in R was used to analyze and visualize the relevant information, including citation counts, country distributions, authors, journals, and thematic analysis. Correlation and comparison analyses were performed using SPSS software.ResultsThe top 100 influential manuscripts were published between 2000 and 2021, with a total citation of 40,662. The average number of citations annually increased over the years and was significantly correlated to the year of publication (r = 0.481, p < 0.01, Spearman’s rho test). The United States was involved in the highest number of publications (n = 42). The number of publications in the journal was not significantly related to the journal’s latest impact factor (r = 0.016, p > 0.05, Spearman’s rho test). Co-occurrence network and thematic analysis identified several important areas, such as microbial metabolites of short-chain fatty acids and overlaps with irritable bowel syndrome.ConclusionThis bibliometric analysis provides the key information of the most influential studies in the area of ASD and gut microbiota, and suggests the hot topics and future directions. The findings of this study can serve as a valuable reference for researchers and policymakers, guiding the development and implementation of the scientific research strategies in this area.